Generation of annotated multimodal ground truth datasets for abdominal medical image registration - Bauer, Dominik F.; Russ, Tom; Waldkirch, Barbara; Tönnes, Christian; Segars, William P.; Schad, Lothar R.; Zöllner, Frank G.; Golla, Alena-Kathrin (International journal of computer assisted radiology and surgery, 2021)
Sparsity of annotated data is a major limitation in medical image processing tasks such as registration. Registered multimodal image data are essential for the diagnosis of medical conditions and the success of interventional medical procedures. To overcome the shortage of data, we present a method that allows the generation of annotated multimodal 4D datasets.